Liar, liar … sometimes: Understanding social-environmental influences on the development of lying. (October 2022) - Talwar, Victoria; Crossman, Angela
Abstract: Lying is a behavior that, in theory, is discouraged and punished, except when it isn't. Perhaps as a result, many individuals lie at low levels somewhat regularly. While research has well documented the cognitive skills that support children's early lying, it does not explain how children learn when to lie versus tell a truth. The current article reviews the impact of social-environmental influences on the development of children's lie-telling knowledge, understanding and behavior, including the roles of parents, siblings, teachers and others. It is argued that holistic examinations of cognitive, social, environmental, cultural and child factors, interacting over time, is required to understand divergent trajectories of lying and truth-telling across development, particularly at the extremes.